Characterization and antioxidant properties of chitosan film incorporated with modified silica nanoparticles as an active food packaging. (30th March 2022) - Dong, Wenxia; Su, Jiaqi; Chen, Yulu; Xu, Duoxia; Cheng, Lei; Mao, Like; Gao, Yanxiang; Yuan, Fang
Highlights: Two different size of the modified silica nanoparticles were successfully synthesized. Modified nanoparticles were incorporated into chitosan to prepare composite films. The mechanical and barrier properties of composite films were significantly improved. The composite films showed strong antioxidant activity. Abstract: In this study, two modified silica nanoparticles (SiO2 -GA NPs) were successfully obtained by covalently grafting gallic acid onto silica nanoparticles. The mean particle diameters of their were 112.7 ± 0.55 nm (1-SiO2 -GA NPs) and 408.7 ± 3.20 nm (4-SiO2 -GA NPs), respectively. Novel antioxidant active packaging composite films were prepared by incorporation of 1-SiO2 -GA NPs or 4-SiO2 -GA NPs into chitosan. The structure analysis of the composite films showed that intermolecular hydrogen bonds were formed between the two modified silica nanoparticles and chitosan. Compared with the chitosan film, the mechanical properties, water vapor barrier property and UV light barrier ability of the composite films were significantly improved. Moreover, the incorporated of the two modified silica nanoparticles significantly increased antioxidant activity of the composite films. This study indicates that composite films incorporated with modified silica nanoparticles, especially the incorporation of 1-SiO2 -GA NPs can be used as novel antioxidant food packaging composite films.